Assessment of the potential of Vachellia seyal and Prosopis chilensis for the reclamation of saline soil lands in the peanut basin production of Senegal - Thiao, Mansour; Sene, Godar; Ndiaye, Moustapha; Sylla, El Hadji Samba Ndao (Frontiers in Plant Science, 2022)
Soil properties and microbial activities are indicators that shape plant communities and evolution. We aimed to determine the interdependency between trees, belowground herbaceous, soil characteristics and arbuscular mycorrhizal communities. Vachellia seyal and Prosopis chilensis and their associated herb layers were targeted. Soil sampled beneath trees and outside canopies were subjected to physicochemical and microbial characterization. Randomly collected living roots of trees and dominant herbs were checked for arbuscular mycorrhizal colonization. A tree seedlings nursery was conducted using black bags filled with following substrates: natural soil 100%, soil mixed with leaf tree plants (LTP) as organic matter at 10%, soil mixed with LTP at 20%, soil mixed with LTP at 30%, and soil mixed with LTP at 50%. As results, the presence of trees improves both herb richness and diversity. Soil mycorrhizal inoculum potentials are higher beneath V. seyal than P. chilensis and decreased significantly with increasing distance from trees. The soil MIP decreased with increasing organic matter content for both tree species but was more pronounced for P. chilensis. Soil salinity is lower beneath V. seyal and higher under P. chilensis and outside canopies. Soil fertility parameters such as carbon, nitrogen, available phosphorus are higher beneath trees then decreased as the distance to trees increases. We conclude that microbial communities, soil properties and herb richness and diversity increased beneath trees but decreased with increasing distance from trees. This effect should be tree species dependent as P. chilensis increased soil salinity and decreased belowground density of herb.